School Choice and Neighborhood Sorting: Equilibrium Consequences of Geographic School Admissions - Ellen Greaves; Hélène Turon (Institute of Labor Economics (IZA), 2024)
Geographic school admissions criteria bind residential and school choices for some parents, and could create externalities in equilibrium for non-parents through displacement or higher rent. Through a dynamic structural model, we show that the policy decision of geographic versus non-geographic school admissions criteria has important implications for equilibrium outcomes in school and housing markets. Geographic admissions criteria segregate schools, but integrate neighborhoods according to income. Incorporating non-parents into the model challenges the existing understanding of how public schools affect the housing market: non-parent households dampen the equilibrium price premium around popular schools; non-parent households are never better off under geographic admissions.
Keywords: I21; I24; R21; 330; school choice; residential choice; school admissions criteria